Syarat dan Kedudukan Pendidik Perspektif Hadits Nabi Muhammad - Agil Husain Abdullah; Ramlianto; Abbas Baco Miro; Rahmi Dewanti (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study examines the requirements and status of educators from the perspective of the hadith of Prophet Muhammad ﷺ. The study aims to analyze the concept of educators, their ideal characteristics, and their strategic position within the Islamic education system based on educational (tarbawi) hadiths. A qualitative approach with library research and thematic (maudhu’i) analysis was employed. Data were collected from hadith compilations and Islamic education literature and analyzed using qualitative descriptive methods. The findings indicate that the Prophet’s hadiths place educators in a noble and strategic position, with key requirements including mastery of knowledge, sincerity, noble character, patience, and exemplary conduct. This holistic concept of educators remains highly relevant for strengthening the professionalism and integrity of Islamic educators in the modern era.AbstrakPenelitian ini mengkaji syarat dan kedudukan pendidik dalam perspektif hadits Nabi Muhammad ﷺ. Penelitian ini bertujuan untuk menganalisis konsep pendidik, karakteristik ideal, serta posisi strategis pendidik dalam sistem pendidikan Islam berdasarkan hadits-hadits tarbawi. Penelitian menggunakan pendekatan kualitatif dengan metode kepustakaan dan analisis tematik (maudhu’i). Data diperoleh dari kitab-kitab hadits dan literatur pendidikan Islam, kemudian dianalisis secara kualitatif-deskriptif. Hasil penelitian menunjukkan bahwa hadits Nabi menempatkan pendidik pada kedudukan yang mulia dan strategis, dengan syarat utama meliputi penguasaan ilmu, keikhlasan, akhlak mulia, kesabaran, dan keteladanan. Konsep pendidik dalam hadits bersifat holistik dan relevan untuk penguatan profesionalitas serta integritas pendidik Islam di era modern.